Antimicrobial activity of ozone. Effectiveness against the main wine spoilage microorganisms and evaluation of impact on simple phenols in wine. (27th March 2013) - Guzzon, R.; Nardin, T.; Micheletti, O.; Nicolini, G.; Larcher, R.
Abstract Background and Aims Microbial contamination affects winemaking, especially after fermentation, e.g. wine ageing in barrels or in contact with oak pieces, when spoilage microbes find an environment favourable for their development. Ozone was evaluated as a sanitising agent in order to assess its potential to prevent microbial spoilage occurring during ageing of wine in barrels using a model system based on barrel wood. Methods and Results Fifty microorganisms of oenological significance were evaluated for their spoilage potential in the barrel. Ethanol resistance, biofilm formation and production of volatile phenols were studied using physiological tests. The effectiveness of ozone in eliminating microorganisms was evaluated in aqueous solution at several cell and ozone concentrations. At a high cell concentration, the presence of organic matter reduced the effectiveness of ozone. At a cell concentration of under 103 CFU/mL, typical of wine cellars, ozone was able to eliminate microorganisms. Resistance to ozone was observed in diverse microorganisms, and this feature is linked to their ability to produce a biofilm. The reduction in simple phenols obtained from oak wood was tested by treating oak chips, routinely used in the wine industry, with an increasing dose of ozone. There was no statistical difference in the phenolic composition of wine treated with six commercial chips. Only a significant exposure of the chips to ozone caused a 33%reduction in the initial content of gentisic acid. Conclusions Ozone was shown to be a highly effective sanitising agent without interfering with the profile of the phenolic substances extracted from oak. The application of ozone for barrel sanitising may be a feasible solution for the prevention of wine spoilage during ageing in oak barrels. Significance of the Study A survey of the effect of ozone on a large number of microorganisms and phenolic compounds of oenological significance, considering some technological variables, is reported.